Improving Indonesian Learning Outcomes in Describing Objects Through Group Games in Grade 2 Students of SD Islam Arofah 1 Boyolali Integrated - Sulistyani, Deni (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The purpose of this study was to improve the learning achievement of the Indonesian language on object description material using a group game approach in class II students of SD Arofah Boyolali, Academic Year 2018/2019. This research action was carried out through two cycles, each - each cycle consisting of planning, action, observation, and reflection. The data obtained in this study included: teacher activity in the learning process obtained from the observation sheet, student activity while participating in the KBM obtained from the observation sheet, and student achievement obtained from the evaluation results at the end of each cycle. The subjects of this study were class II students of SD Arofah Boyolali with a total of 34 students consisting of 17 male students and 17 female students. Based on the analysis of the data, it was found that the results of the study in cycle I showed that student learning outcomes were still low, with a mastery learning percentage of 79.41% and the average evaluation result for one class of students was 80. In cycle II, it was found that student learning outcomes had increased by obtaining a mastery learning percentage of 88.24% and the average grade of student evaluation results in one class got 83. The results of this study, it can be concluded that the use of a group game approach can improve the learning outcomes of Indonesian language material description of objects in class II students of the Integrated Islamic Elementary School Arofah Boyolali Academic Year 2021/2022.